Synthesis of optimal multidimensional digital filter - Буриченко, М.; Градобоєва, Н. В.; Держак, C. B.; Сольонов, В. І. (Proceedings of National Aviation University (archive), 2000)
Demonstrated is one of efficient methods of digital realization of analogue multidimensional filter. Worked out on the basis of this method is software of digital realization of analogue multidimensional filter. The efficiency of the proposed method is demonstrated by the example of digital realization of optimal filter structure in the channel of angular velocity measurement of snap down inertia navigation